Assessing the Implementation of a City for All within the New Indonesian Capital City: Smart and Green City Perspective - Wasisto Raharjo Jati; Choerunisa Noor Syahid; Ayu Nova Lissandhi; Yusuf Maulana (Journal of Regional and City Planning, 2023)
The ‘city for all’ concept shows how the new Indonesian capital city Nusantara is expected to create a harmonious and inclusive relationship between its residents and its surrounding environment. There is still a long way to go towards its implementation, as there are many unsolved environmental problems related to the new capital city project. In line with the previously-mentioned statement, this study analyzed the feasibility of implementing the city for all concept in the new capital city in view of the existing environmental issues in East Kalimantan. Another objective of this research was to see whether the city for all concept is compatible with the local context. These two research objectives were pursued by using the ‘smart city’ and ‘green city’ perspectives to assess the current development progress. We used qualitative research methods, including fieldwork and in-depth interviews with various actors in both the national and local context, as well as intensive archival research. This study revealed that there is a discrepancy in vision between the government, the city planners, and the locals in East Kalimantan. Furthermore, the locals, especially indigenous people, have shown a lukewarm response to the capital city project. Based on the fieldwork, it seems that the city for all concept and the currently existing smart and green city components do not match. This study concludes that solving the current environmental problems and unequal social participation should be done first before carrying on with the capital city development planning.